Designing a Mindful Self-Compassion Protocol Based on the Lived Experiences of Adolescents with Self-Injurious Behaviors - Fallahmanesh, Elham; Ghamari, Mohammad; Vakili, Samira; Gholami Toran Poshti, Marzieh (International Journal of Education and Cognitive Sciences, 2026)
Purpose: This study aimed to design a culturally and developmentally appropriate mindful self-compassion training protocol based on the lived experiences of adolescents with self-injurious behaviors.Methods and Materials: A qualitative phenomenological approach was adopted to explore the emotional, cognitive, and behavioral needs of adolescents engaged in non-suicidal self-injury (NSSI). Twenty-two adolescents aged 13 to 18 from Tehran participated in semi-structured, in-depth interviews. Sampling continued until theoretical saturation was achieved. Thematic analysis was conducted using NVivo software (version 14) to identify recurring themes and construct the core components of the training protocol. Based on the extracted themes, a ten-session mindful self-compassion protocol was developed. Content validity was assessed using CVR and CVI, and inter-rater reliability was measured using the Kappa coefficient, with input from a panel of 12 experts in adolescent psychology and curriculum design.Findings: Six main thematic domains emerged from the data: emotional awareness and acceptance, self-kindness, mindful presence, safe emotional expression, interpersonal support, and values and identity. These themes were translated into a ten-session intervention structure targeting emotional literacy, inner dialogue transformation, mindfulness practice, peer support, and value-based identity reconstruction. The content validity ratio (CVR) ranged from 0.86 to 0.93, the content validity index (CVI) from 0.92 to 0.96, and the Kappa coefficient from 0.82 to 0.89, confirming the protocol’s conceptual relevance and expert consensus.Conclusion: The study offers a context-sensitive, empirically grounded, and experientially informed intervention protocol for adolescents with self-injurious behaviors. By grounding the protocol in adolescents’ lived experiences and validating its content through expert review, this study provides a valuable tool for mental health professionals aiming to address NSSI through mindful self-compassion approaches tailored to developmental and cultural contexts.